Apariencia y realidad en la escritura - Marrone, Caterina (Escritura e Imagen, 2007)
Simulation is a specificity of human being just like writing is a specific feature human beings. These two specificities can be interwoven when one wants to hide writing message. The concealment of this message can be done in two ways, one called steganography, that is through techniques that hide the message itself to those who are not meant to receive it, the other is cryptography, that is acting on the signifier. Our alphabetical forms of writing, including the syllabic ones, are fit to be counterfeited and transformed into cryptographies because the level of expression signifier can be altered by mixing the letters constituting its structure. There are several ways to make cryptography of a text. They follow precise mathematical rules based on the discreteness of alphabetical characters that, for their own nature, can be treated as numbers. In addition, alphabetical-linguistic systems share with numbers many characteristics. In this essay we deal with different systems of written codes: the monoalphabetical and polialphabetical ones developed by Leon Battista Alberti, the Table of Vigenère, as well as some more recent methods for producing ciphers along with their resolution. But if we can operate in such analytic way on the signifier, for its nature of discrete element, what happens in case of non-alphabetical or non-syllabic forms of writings? In the Ptolemaic period (but even before) there were many cryptographies in hieroglyphic writing composed with Egyptian ideograms – i.e. in a figurative form of writing – that did not have the discreteness and referred both to content and phonetic, mixing them together. This essay examines one of these cryptographies and other engraved on the flat surface of the scarabs preserved in some museum collections and analyzed by the Egyptologist E. Drioton. Starting from some observations we have drawn two final considerations on Egyptian cryptography: 1) that it uses exclusively phonology by dealing with ideograms as they were phonemes in a similar way of alphabetical cip- hers, and 2) that alteration – i.e. the change in position to create unusual geometries – allowed the Egyptians to change, in a general way, the syntactic order of signs so to assimilate hieroglyphs to alphabetical writing. In my opinion, this subject should be further analyzed for it could lead us to new interesting linguistic and semiotic developments.